Asuhan Keperawatan Pada Ny. S Dengan Gangguan Sistem Muskuloskeletal : Post Op ORIF Fraktur Sepertiga Radius Distal Dextra Di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Afifah Ismatul Maula; Ahmad Zakiudin (STIKES Columbia Asia Medan, 2026)
Background: Distal radius fracture is the most common fracture of the radius bone near the wrist joint. The prevalence of fractures in Indonesia in 2024 was 3.8%, indicating that approximately 20 million people experienced fractures. Therefore, nursing care planning is required to address musculoskeletal disorders. Objective: To describe the nursing care for patients with Musculoskeletal System Disorders: Post-Op ORIF Fracture of One-Third Distal Radius Dextra. Method: This study used a descriptive narrative method by providing an overview of nursing care through a nursing process approach. Results: Nursing diagnoses that emerged in the patient included acute pain, impaired physical mobility, risk of infection, and knowledge deficit. Interventions performed included pain management, mobilization support, infection prevention, and health education. Conclusion: After two days of nursing implementation, one diagnosis was fully resolved and three diagnoses were partially resolved due to time constraints. Discharge planning was provided including deep breathing relaxation techniques, passive ROM exercises, and wound dressing changes every two days.